2006
DOI: 10.1093/humrep/del049
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of nuclear vacuoles in human sperm selected for ICSI affect pregnancy outcome?

Abstract: Microinjection of vacuolated sperm appears to reduce the pregnancy rate and appears to be associated with early abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
149
0
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 18 publications
6
149
0
14
Order By: Relevance
“…It has been reported that the negative impact of large nuclear vacuoles (LNV) is perceptible after the onset of the EGA, leading to reduced blastocyst formation [28][29][30][31]. Moreover, LNV also affect ongoing pregnancy rates [31][32][33][34], miscarriage rates [31,33,[35][36][37], and malformation in offspring [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the negative impact of large nuclear vacuoles (LNV) is perceptible after the onset of the EGA, leading to reduced blastocyst formation [28][29][30][31]. Moreover, LNV also affect ongoing pregnancy rates [31][32][33][34], miscarriage rates [31,33,[35][36][37], and malformation in offspring [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the IMSI procedure is positively associated with implantation and pregnancy rates [2][3][4][5][6][7][8][9]. In addition, recent meta-analysis showed that the IMSI procedure is associated with improved embryo quality [10], implantation [10,11] and pregnancy rates [10][11][12], as well as lower miscarriage rates [10,11] in couples with male factor [10][11][12] and previous ICSI failures [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It enables the accurate, real-time selection of motile "top spermatozoa" with a morphologically and morphometrically normal head [1,4,7]. When available, vacuole-free spermatozoa or spermatozoa presenting a single, small vacuole [6] that occupies less than 4 % of the total head area [10,31] can then be used for intracytoplasmic morphologically selected sperm injection (IMSI) [7]. It has been suggested that in patients with ICSI cycle failures, implantation efficiency and pregnancy rates may be increased by the use of IMSI [1].…”
Section: Introductionmentioning
confidence: 99%